2023
DOI: 10.37190/ppmp/163418
|View full text |Cite
|
Sign up to set email alerts
|

Substitution mechanism of rare earths at fluorapatite characteristic sites: experimental and computational calculations

Abstract: Rare earths (REs) containing phosphate rock is a potential REs resource. The unclear occurrence mechanism of REs in phosphorite limits its further development and utilization. Fluorapatite (FAP) is the main REs-bearing target mineral in phosphorite, the microscopic mechanism of REs entering FAP still needs to be further studied from the electronic scale. In this paper, the doping mechanism of REs in FAP was studied by experiment combined with GGA+U calculation. The XRD, SEM, and FT-IR characterization results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…When the element content was too low, the obtained data had a poor signal‐to‐noise ratio and could not extract useful information. Meanwhile, because all REEs were replaced in the form of isomorphism in Fap, they had similar occurrence forms in phosphorite 31,32 . The changes of yttrium in different phases before and after leaching were similar to other REEs.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…When the element content was too low, the obtained data had a poor signal‐to‐noise ratio and could not extract useful information. Meanwhile, because all REEs were replaced in the form of isomorphism in Fap, they had similar occurrence forms in phosphorite 31,32 . The changes of yttrium in different phases before and after leaching were similar to other REEs.…”
Section: Resultsmentioning
confidence: 79%
“…Studies have shown that the contents of REEs increased with the increase of Fap content, 9,29 but there was no evidence to suggest that it increased with the increase of Dolo content 30 . It was currently recognized that REEs mainly replace calcium atoms in Fap in the form of isomorphism, 31,32 and the content of REEs was often positively correlated with the content of Fap. Dolo contained a certain amount of REEs, but compared with Fap, the content of REEs in Dolo was very low.…”
Section: Methodsmentioning
confidence: 99%